Pharmacists' and Type 2 Diabetes Mellitus Patients' Perceived Barriers to Insulin Therapy at Hospital: A Qualitative Study - Suastini, Ni Made; Gayatri, Ni Putu Ayu Deviana (Babali Nursing Research, 2025)
Introduction: Recent data show that Indonesia ranks fifth in the world for diabetes mellitus (DM). An increase in insulin use accompanies the increasing prevalence of DM. However, several barriers to insulin use remain among patients and healthcare professionals, impacting blood glucose control. This study explored perceptions of barriers to insulin therapy among T2DM patients and hospital pharmacists. Methods: This research was a qualitative study. The recruitment of participants used a consecutive sampling method. Eighteen in-depth interviews were conducted with T2DM patients, and nine were conducted with hospital pharmacists at a private hospital. Thematic analysis was used to generate findings in this research. Results: Barriers faced by patients in insulin therapy include fear and anxiety, insulin use practices, and misconceptions about insulin. Meanwhile, the results of the barriers faced by pharmacists on providing education and consultation on insulin therapy included patient, facility, and system barriers. These factors can impact insulin therapy and target outcomes in T2DM patients. Conclusion: Barriers from the patient and pharmacist perspectives are very important to assess, so that comprehensive therapy in the form of collaboration between health workers and patients can be implemented to achieve the target outcomes for T2DM patients.